Professional Teacher: Study of Tarbawi Tafsir - Siti Nurul Mutiah; Cecep Anwar; Hafid (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to find the concept of professional educators in the Qur'an and analyze Law No. 14 of 2005. This study uses a descriptive qualitative approach. The results of this study are: strengthening the idea of ​​educators based on law. There are words Al-Mu'allim, Al-Murobbi, and Al-Muzakki in the Qur'an which mean educating, teaching, guiding, directing, training, and evaluating. These terms are included in the term educator in formal education. The responsibility of a teacher is not only to students, but to parents of students, society, nation and religion. Teachers are obliged to provide and plan learning well and orderly and develop their skills and abilities continuously. Teachers who carry out their duties well are called professional gueu, namely teachers who have many skills according to the above law regarding teachers and lecturers in article 10 paragraph 1 which states that skills include pedagogical, personality, social and professional.